Study of the Essential Oil Composition of Lallenmantia iberica (M. Bieb.) Fisch and CA Mey. (Lamiaceae) from Turkey - Yuce, E.; Bagci, E. (Asian Journal of Chemistry, 2012)
The essential, oil of wild-growing Lallemantia iberica (Lamiceae) from Turkey was obtained by hydrodistillation and analyzed by GC and GC-MS. In the oil of the Lallemantia iberica, 40 components were characterized representing 90.1 % of the total oil, with germacrene-D (36.0 %), beta-caryophyllene (18.3 %) and bicyclogermacrene (9.7 %) as the main constituents. The results showed that the analysis of essential oil composition will add some contributions on the usability of this plant as a crop and renewable resources and chemotaxonomy of the genus patterns.
Keywords: Lallemantia iberica; GC-MS; Essential oil; Germacrene D